Nursing experience of a patient with pain caused by periarthritis of the shoulder treated with the combined application of Traditional Chinese Medicine characteristic nursing techniques (中医特色护理技术联合应用治疗1例肩周炎疼痛患者的护理体会) - LI Yuye (李玉叶); PAN Lei (潘磊); SHEN Juan (沈娟); ZHANG Yuanyuan (张园园); DOU Jinjie (窦金杰); TANG Ling (唐玲); E Haiyan (鄂海燕) (Journal of International Translational Medicine Limited, 2022)
This paper summarized the nursing experience of a patient with pain caused by periarthritis of the shoulder treated with the combined application of Traditional Chinese Medicine (TCM) characteristic nursing techniques. Followed by the auricular acupoint massage, the auricular acupoint blood-letting therapy was performed to relieve the shoulder pain and discomfort. The auricular acupoint sticking and pressing therapy showed a long-term stimulation effect, while the balanced cupping therapy was able to enhance the local stimulation effect. The combined application of TCM characteristic nursing techniques are effective in relief of pain in patients with acute periarthritis of the shoulder, which is worthy of promoting. (本文总结了中医特色护理技术联合应用治疗1例肩周炎疼痛患者的护理体会。在耳部按摩的基础上进行耳穴放血, 以减轻肩关节疼痛和缓解肩关节不适, 耳穴贴压则可以起到持续刺激的作用, 平衡火罐作用于局部, 以达到加强刺激的效果。联合疗法能够更好地缓解肩周炎发作期患者的疼痛症状, 值得临床借鉴。)